Evaluation of Clinical Effectiveness and Subjective Satisfaction of a New Toothbrush for Postsurgical Hygiene Care: A Randomized Split-Mouth Double-Blind Clinical Trial - Marco Montevecchi; Annalisa Moreschi; Maria Rosaria Gatto; Luigi Checchi; Vittorio Checchi (The Scientific World Journal)
The aim of this RCT was to evaluate plaque control and gingival health promotion effectiveness of a new toothbrush with extra-soft filaments in postsurgical sets. Ten consecutive patients with at least two scheduled symmetrical periodontal surgeries were selected. Following the first periodontal surgery, a test (TB1) or control (TB2) toothbrush was randomly assigned. After the second surgery, the remaining toothbrush was given. Patients were asked to gently wipe the surgical area from days 3 to 7 postoperatively and to gently brush using a roll technique from day 7 till the end of the study. Baseline evaluation took place on the day of surgery and follow-ups were performed at days 7, 14, and 30 postoperatively. A more evident PI reduction was recorded for test toothbrush where a regular decrease was observed till day 14; then, this parameter tended to stabilize, remaining however lower than that recorded for the control toothbrush. There were no statistical differences in the GI between test and control toothbrushes. All patients introduced the test toothbrush at surgical site at third day; the control toothbrush was introduced within a mean of 9 days. The introduction of the test toothbrush 3 days after periodontal surgery may be recommended.